PERAN BISNIS JUAL BELI ONLINE DALAM PENINGKATAN PEREKONOMIAN KELUARGA: STUDI PADA PERUMAHAN PESONA PERMATA GADING 1 SIDOARJO - Ilmiati Lina Sahvitri (Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study was conducted to determine the role of online buying and selling businesses in improving the family economy in Pesona Permata Gading 1 Sidoarjo Housing. The method used to collect data is by means of a descriptive qualitative method. This method aims to obtain data by using, observation, interviews or interviews, as well as documentation. The technique used to collect data in this research is to conduct study literature techniques or obtain information data from other reference sources, interviews to obtain research data are carried out by asking questions to several interviewees, direct observation or research on people who have selling businesses. buy online, as well as documentation. The results showed that the role of the online buying and selling business had a major impact on improving the family's economy in the Pesona Permata Gading 1 Housing in Sidoarjo. With the existence of this online buying and selling business, this economic improvement continues to increase from time to time from what has previously experienced a decline in this housing. With various efforts made by the community, it is also possible to realize a family economy that continues to increase at Pesona Permata Gading 1 Sidoarjo Housing.